Hallazgos frecuentes de las acciones de control en la Municipalidad Provincial de Ucayali – Contamana periodo 2019 – 2023 - Dávila Sánchez, Antonio Miguel (2025)
The control actions carried out by the responsible body aim to guarantee the correct use of public funds by the different state entities. The purpose induced by this research is to identify the frequent findings of the control actions in the Provincial Municipality of Ucayali - Contamana, in the period 2019 - 2023. Guided by this ideal, the current master's thesis is developed, which is Quantitative, Descriptive level and Non-experimental design. After analyzing the data, the following conclusions were reached: the recurring finding evidenced in the control actions executed in the Provincial Municipality of Ucayali - Contamana is Functional Administrative Responsibility detected on 43 occasions, which is equivalent to 42.16% of the total. On the other hand, the type of oversight service most frequently applied in the aforementioned municipal institution is Simultaneous Oversight, which was implemented 87 times during the five-year period investigated, representing 71.31% of the total. Similarly, the Post-Oversight actions executed showed that the most frequently repeated finding was Functional Administrative Responsibility, which was found 11 times, equivalent to 42.31%. It was verified that the Municipality reports the highest number of amendment actions as Not Corrected (71.10%).